Supramolecular Double-Helical Polymers: Supramolecular Chiral Induction and Asymmetric Catalysis - Xiaojun Guo; Xinyu Jia; Qin He; Wengui Duan; Yanjun Zhang; Yan Huang; Luzhi Liu (Molecules)
Seeking a supramolecular chiral system induced by trace chiral molecules instead of traditional complex and expensive chiral ligands to achieve high yield or ee value conversion of the products is of great significance in asymmetric synthesis but still remains a challenge. Herein, two types of double helical supramolecular chiral systems, (M)-Helix and (P)-Helix, with opposite chiral optics were constructed in situ using tyrosine-functionalized pillar[5]arene as inducers. These systems exhibit chiroptical stability and enable remarkable chirality amplification from 7 mol% chiral seeds. When applied to intermolecular olefin cyano-trifluoromethylation, (M)-Helix exhibits remarkable catalytic efficiency (yield up to 89%), whereas (P)-Helix achieves higher enantioselectivity (ee up to 84%). This research will provide new ideas for supramolecular chiral catalysts in organic asymmetric catalysis applications.